Oral Squamous Cell Carcinoma arising from Lichenoid Contact Reaction: A Case Report - Khatiwada, Kripa; Rimal, Jyotsna; Maharjan , Iccha Kumar; Regmee, Pragya; Adhikari , Sagar; Keshwar, Shashi (Journal of BP Koirala Institute of Health Sciences, 2022)
Lichenoid contact reaction is a type of delayed hypersensitivity reaction to constituents derived from dental materials. It may occasionally transform into oral squamous cell carcinoma. A 62-year-male reported with the chief complaint of a wound in the inner aspect of right cheek for 2 weeks. On initial examination, a diffuse erythematous area with interspersed non- scrapable white striae was present on the right buccal mucosa and residual alveolar ridge with respect to 47 extending till gingivobuccal aspect of 45, roughly linear in shape, approximately 3x1 cm2 in size, with a rough overlying surface. Ointment triamcinolone 0.1% was prescribed for 1 week. The patient visited after 3 months. Clinical examination revealed an ulcer with peripheral induration of size approximately 2.5 mm on right buccal mucosa adjacent to 46. An incisional biopsy revealed oral squamous cell carcinoma. Long-term follow-up of patients with oral lichenoid reaction is mandatory for early detection of malignant transformation.